The unofficial guide to Macromedia Dreamweaver 8 - Kyle, Lynn (Wiley Publishing, 2006)
You can dream big with Macromedia's robust Dreamweaver Web design software, but to use it with confidence you need to understand its quirks and shortcuts. Find out what the manual doesn't always tell you in this insider's guide to using Dreamweaver in the real world. Must you know HTML to design Web pages? How do the pros add data to Web sites? From working with frames and forms to jumping into multimedia ina big way--first get the official way, then the best way from an expert. Watch for these graphic icons in every chapter to guide you to specific practical information. * Bright Ideas are smart innovations that will save you time or hassle. * Hacks are insider tips and shortcuts that increase productivity. * When you see Watch Out! heed the cautions or warnings to help you avoid commonpitfalls. * And finally, check out Inside Scoops for practical insights from the author. It's like having your own expert at your side!